2021
DOI: 10.1136/bmjopen-2020-041659
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of the prevalence of obesity and overweight among women in Ghana

Abstract: ObjectiveIdentifying hot spots for the overweight aids in effective public health interventions due to the associated public health burden and morbidities. This study, therefore aimed to explore and determine the spatial disparities in the overweight/obesity prevalence among women in Ghana. The study also aims at modelling the average body mass index (BMI) values using the spatial regression and the performance compared with the standard regression model.DesignThis is a cross-sectional study using data from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 40 publications
5
19
0
Order By: Relevance
“…Our estimate of the BMI of women in Accra in 2010 was similar to what was found in the 2006 WHO STEPs survey [ 37 ] and was higher than the estimated national average for Ghanaian women at that time [ 7 ], which is consistent with the evidence of higher BMI in urban compared with rural areas in Ghana [ 18 ] and SSA [ 11 ]. Similarly, the prevalence of women with uncontrolled hypertension in Accra was slightly higher than the crude prevalence among women in Ghana [ 5 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our estimate of the BMI of women in Accra in 2010 was similar to what was found in the 2006 WHO STEPs survey [ 37 ] and was higher than the estimated national average for Ghanaian women at that time [ 7 ], which is consistent with the evidence of higher BMI in urban compared with rural areas in Ghana [ 18 ] and SSA [ 11 ]. Similarly, the prevalence of women with uncontrolled hypertension in Accra was slightly higher than the crude prevalence among women in Ghana [ 5 ].…”
Section: Discussionsupporting
confidence: 86%
“…Higher SES and literacy were associated with higher BMI and lower BP. This divergent trend between BP and BMI has been found in other studies in SSA [ 10 , 15 18 , 38 41 ]. Higher SES in SSA may lead to a higher caloric consumption and less energy expenditure in work and commute (e.g., commuting by private car [ 42 ]) that are risk factors for elevated BMI [ 15 , 43 ].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This is a worry for public health due to the risk of maintaining overnutrition status in adulthood together with the several negative consequences. The study also found that a child's age (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), birth weight (greater than 4 kg), consumption of protein foods, and mothers' wealth status are signi cantly associated with the risk of overweight and obesity among children under-ve years in Egypt. These ndings indicate the need for early and urgent strategies to mitigate childhood overnutrition in Egypt.…”
Section: Declarationsmentioning
confidence: 86%
“…Indeed, a country such as Ghana recorded as high as 65% increase in obesity during the study period [2]. Other studies also observed alarming trends in obesity among women of reproductive age in the African region (8-9). There is a need for deliberate policies by governments to address the problem.…”
Section: Introductionmentioning
confidence: 99%